Autonomous KIWI Bot for Industrial Application (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents the design and development of a fully autonomous KIWI bot equipped with a robotic arm for industrial applications. The robot is designed to transport objects from one location to another efficiently. It features a bucket for carrying loads, which can be placed and retrieved using the robotic arm. The system is powered by an ESP32 microcontroller and controlled via both autonomous navigation and a custom-designed application for manual operation. The KIWI bot is equipped with high-torque motors, a LiDAR sensor for obstacle detection, and servo-driven actuation mechanisms to ensure precise object manipulation. This research focuses on the hardware and software integration of the system, its operational workflow, and potential industrial use cases.
Keywords: Autonomous Navigation; Robotic Arm; ESP32 Microcontroller; LiDAR Sensor; Industrial Automation